2016
DOI: 10.1002/micr.30128
|View full text |Cite
|
Sign up to set email alerts
|

Recipient bone marrow‐derived stromal cells prolong graft survival in a rat hind limb allotransplantation model

Abstract: BMSCs induce T cell hyporesponsiveness and prolong graft survival in the rat vascularized composite allotransplantation model. BMSCs exhibit immunomodulatory properties against acute rejection that can be realized without the need for significant recipient immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…When considering clinical settings, donor‐derived MSCs face the potential problem of their future applicability, in terms of the associated invasive procedure and the brain‐dead donor. On the other hand, recipient‐derived MSCs provide the distinct advantage of easy access, nonimmunogenicity, and cell preparation or even pretreatment ahead of transplantation (Cheng et al, ; Ikeguchi et al, ). In animal experiments in this study, we used human iMSCs to investigate their immunomodulatory effects in the rat VCA model for future clinical situations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When considering clinical settings, donor‐derived MSCs face the potential problem of their future applicability, in terms of the associated invasive procedure and the brain‐dead donor. On the other hand, recipient‐derived MSCs provide the distinct advantage of easy access, nonimmunogenicity, and cell preparation or even pretreatment ahead of transplantation (Cheng et al, ; Ikeguchi et al, ). In animal experiments in this study, we used human iMSCs to investigate their immunomodulatory effects in the rat VCA model for future clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples from each recipient rat were taken within 2 days before transplantation, and at 10, 14, and 17 days after transplantation. Approximately, 250 μl of blood was obtained from each recipient's caudal vein at each time point, and separated plasma samples were stored at −80°C for later ELISA analysis, as described elsewhere (Ikeguchi et al, ; Oda et al, ). Plasma concentrations of IL‐2, IL‐10, TNFα, and IFN‐γ were determined using standard rat ELISA kits (R&D Systems, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they also reported that whole‐limb allografts demonstrated different antigenicity from grafts transplanted as individual components. VCAs sometimes include bone marrow, which contains bone marrow‐derived stromal cells and induces mixed chimerism to some extent (Ikeguchi et al, ). This might reduce the antigenicity when a VCA is transplanted in a whole limb.…”
Section: Discussionmentioning
confidence: 99%